Children’s Identity and the Politics of Representation in Comics: Strengths and Weaknesses (Study by Maria Nikolajeva) - Rohmah, Zazirotur; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study analyzes the formation of children’s identity and subjectivity in the comic "Kelebihan di Balik Kekurangan" (Excess Behind Disadvantages) using Maria Nikolajeva’s theory. This study aims to explore how the narrative structure, characterization, and child-adult relationships represent the process of children’s identity formation in a social context that emphasizes difference and self-acceptance. Nikolajeva’s theoretical approach focuses on three main aspects: voice (the child’s voice), agency (the ability to act), and representation (the child’s representation in the text). The analysis shows that the comic not only raises the issue of social inequality but also presents a transformative narrative in which children become active subjects who recognize their own worth through experience and reflection. The process of identity formation of the main character depicts a journey from alienation to self-acceptance, showing that shortcomings are not limitations, but rather sources of strength. Through simple yet meaningful narratives and visual symbolism, this work emphasizes the role of children’s literature as a medium for moral, psychological, and social education. This study confirms the relevance of Nikolajeva’s theory in the context of Indonesian children’s literature, while also demonstrating that literary works can function as a humanizing space where children learn empathy, reflection, and appreciation for differences.